Performance improvement making it happen - Enos, Darryl D. (Boca Raton : St. Lucie Press, 2000)
Presents the tools necessary for understanding and measuring performance, and how to improve it. This work offers a comprehensive, practical approach to diagnostic performance problems and their causes. It also gives the tools and methods for achieving major performance improvement in individuals, teams, and organizations.
Includes bibliographical references and index.
oif 18/02/15
Loan
Keywords: Organizational effectiveness; Performance; Teams in the workplace